The Effect of Educational Videos in Javanese Language on the Perception, Interest, and Implementation of the COVID-19 Vaccination in the Elderly - Hidayati, Nur; Rokhman, Abdul; Nafi’ah, Dzakirotun (Babali Publisher, 2023)
Introduction: The coverage of the Covid-19 vaccination for the elderly in Indonesia is low, even though the elderly is a vulnerable group to the severity of Covid-19 infection and is the main focus for increasing their immunity. One of the efforts to increase interest, perception, and implementation of the Covid-19 vaccination in the elderly is by providing education through Javanese-language videos. This study aimed to determine the effect of educational videos with Javanese language on the perception, interest, and implementation of the Covid-19 vaccination in the elderly. Method: The research used a pre-experimental design with one group pre-post test. The population were 182 elderly. The samples of this research were 125 elderly who had not been vaccinated and selected using the cluster random sampling. This research was conducted in Karangdayu Village, Baureno District, Bojonegoro Regency from March to June 2023. The intervention was in the form of playing educational videos with Javanese language about Covid-19. The data were taken through a questionnaire, and then analyzed using the Wilcoxon and McNemar tests (α ≤0.05). Result: The results showed that there was an effect on changes in the perceptions and interests of the elderly in Karangdayu Village, Baureno District, Bojonegoro Regency after being given educational videos about Covid-19 vaccination (p=0.001). Educational videos are effective in increasing the perception and interest of the elderly for the Covid-19 vaccination, and statistically affecting the implementation of the Covid-19 vaccination in the elderly. However, descriptively, providing educational videos in Javanese language has not been able to maximize the number of elderly people to administer the Covid-19 vaccine. It is necessary to study in more depth about the factors that affect the implementation of Covid-19 vaccinations in the elderly besides interests and perceptions.